AIR POLLUTION MANAGEMENT DUE TO COAL LOADING AND UNLOADING ACTIVITIES AT THE MAHAKAM COAL TERMINAL JETTY - Suryadi, Awel; Azzahra, Nabila Putri; Kensiwi, Fitri; Amrullah, Romanda Annas (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2025)
Coal loading and unloading operations at the Mahakam Coal Terminal Jetty in Embalut Village, East Kalimantan, have contributed significantly to local air pollution. Fine coal dust particles are released into the surrounding environment, negatively impacting the health of workers and nearby communities. This study aims to examine the causes of air pollution at the jetty and identify suitable mitigation strategies. A descriptive qualitative approach was applied, with data collected through direct observation, interviews with stakeholders (including operational staff, HSE personnel, and the village head), and documentation of jetty activities and environmental conditions. Data credibility was ensured using triangulation. Results reveal that the main contributor to air pollution is the absence of effective dust control systems, particularly during the loading and unloading processes. Additional factors, such as high wind speeds, intense operational activity, and the lack of buffer vegetation, worsen the pollution levels. Health complaints reported by residents include respiratory issues, eye irritation, and skin problems. While some mitigation efforts such as water spraying systems, dust nets, equipment cleaning, and periodic air quality checks have been introduced, their implementation remains inconsistent. To address this, the study recommends the systematic adoption of Standard Operating Procedures (SOP) and the development of green infrastructure to minimize long-term environmental impacts